An in-vitro comparison on root canal preparation between profile, protaper, flex master rotary techniques and NiTi K-File manual instrumentation - Ashofteh Yazdi K.; Eslami M.; Soleimani A. Sheykh Rezaee MS. (Tehran University of Medical Sciences, 2004)
Statement of Problem: Root canal cleaning and shaping are important steps in endodontic therapy. In"norder to develop better techniques, new instruments are constantly designed and delivered to the market."nPurpose: The aim of the present study was to compare the effectiveness of one manual with three rotary"nroot canal instrumentations techniques."nMaterials and Methods: In this in-vitro study, 80 mesial roots of freshly extracted human mandibular"nmolars were divided in to four groups equally and prepared by one of the following instrumentation"nmethods profile NiTi rotary system, Protaper NiTi rotary system, Flex Master NiTi rotary system and"nhand NiTi K-file instrumentation. In each root one of the canals was instrumented and the other was used"nas control."nAfter decalcification, cross sections at 3mm and 5mm of apical portion were prepared and examined for"nremaining debris, predentin and smooth walls under light microscope. The data were analyzed by"nKxuskal-Wallis test."nResults: Significantly less debris was found at 3mm cross- section using protaper and Flex Master"ntechniques (P<0.05). No significant differences were found at 5mm cross section. Also no significant"ndifferences were observed for remaining predentin at all regions. Significantly more smooth walls were"nfound at both regions using protaper technique (P<0.05)."nConclusion: The protaper technique employed in this study resulted in cleaner root cana! walls than the"nother techniques.